Novel method for detecting the stage of arthrosis and femoroacetabular impingement using a gyroscopic sensor and neural networks - Holeka, Pavel; Studnička, Filip; Štěpán, Jan; Matyska, Jan; Šlégr, Jan; Páral, Jiří; Šmejkal, Karel; Lochman, Petr (Acta chirurgiae orthopaedicae et traumatologiae Čechoslovaca, 2023)
PURPOSE OF THE STUDY Femoroacetabular impingement syndrome is a complex, often post-traumatically developing impairment of the hip joint, characterized by ambiguous symptomatology, which makes early diagnosis diffi cult, especially in the early stages. Experimental retrospective study was carried out to evaluate the usability of a triaxial gyroscopic sensor in routine practice as an additional indication criterion for operative versus conservative treatment procedures. MATERIAL AND METHODS 92 patients were included in the retrospective study, and 62 completed the investigation. All patients signed informed consent. A gyroscopic sensor was placed on the right side of the pelvis above the hip joint, and the patients walked approximately 15 steps. Furthermore, an evaluation of the data during stair climbing and a complete clinical examination of the dynamics and physiological movements in the joint was carried out. Data measured with a gyroscopic sensor were processed using differential geometry methods and then evaluated using spectral analysis and neural networks. The proposed technique of diagnosing FAI using gyroscope measurement is a fast, easy-to-perform method. RESULTS Our approach in processing gyroscopic signals used to detect the stage of arthrosis and post-traumatically developing FAI could lead to more accurate early detection and capture in the early stages. CONCLUSIONS The obtained data are easily evaluated, interpretable and benefi cial in diagnosing the early stages of FAI. The results of the conducted research showed this approach to more accurate early detection of arthrosis and post-traumatically developing FAI. Key words: wearable sensors; osteoarthritis; mathematical biophysics; telemedicine.
Keywords: Femoracetabular Impingement; Osteoarthritis; Joint Diseases; Retrospective Studies; retrospektivní studie; lidé; kyčelní kloub; Neural Networks, Computer; osteoartróza; Hip Joint; femoroacetabulární impingement; nemoci kloubů; Humans; neuronové sítě